Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 month ago

# Pls help and explain?

Relevance
• 1 month ago

5 § (3 § 4)

from 3 § 4

(3 + 4)/(3 x 4) = 7/12

5 § 7/12

(5 + 7/12)/(5 x 7/12) = 67/35 or 1 32/35

Answer is none of the above.

• 1 month ago

Parentheses control the order of operation here, so start with 3 § 4:

3 § 4 = (3 + 4) / (3 × 4) = 7/12

Now, the outer expression becomes:

5 § (3 § 4) = 5 § (7/12) = (5 + 7/12) / (5 × 7/12)

Here, I'd multiply that by 12/12 to cancel out the "divide by 12" on top and bottom:

= (5•12 + 7) / (5 × 7)

= 67 / 35

= 1 32/35

That's not one of the given numbers, so the answer is "(D) None of these".

If you don't multiply by 12/12, you get the same answer, but with a bit more work:

(5 + 7/12) / (5 × 7/12) = (67 / 12) / (35 / 12)

= (67 / 12) × (12 / 35)

= (67 × 12) / (35 × 12)

= 67 / 35   . . . . or 1 32/35 once again

You still end up canceling out 12/12 somehow.

• 1 month ago

If a § b means (a + b)/(a × b) find the value of 5 § (3 § 4).

5 § (3 § 4) = 5 § (3 + 4)/(3 × 4) = (C)   5 7/12

• alex
Lv 7
1 month ago

a#b = (a+b)/(a x b)

so 3#4=(3+4)/(3 x 4)=7/12

so

5#(3#4)=5#(7/12) = [5+(7/12)]/(5 x 7/12) = ...simplify